Pendidikan Islam Berbasis Nilai Tauhid - Hamidah, Dedeh (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
AbstractThe problem that occurs in this digital era is a moral problem. The number of deviations that occur due to the use of technology that is not guided by faith. Like addiction to playing online games, a lot of hoax news is spread, free sex fraud, easy to be pitted against and other crimes. Whereas the national education goal of 60% is to realize spiritual intelligence. This is in line with the goal of Islamic education, which is to become a human being. Humans who are human beings are perfect humans in practicing goodness according to the will of Allah SWT. This study aims to determine Islamic education based on the value of monotheism. The approach used in this study is a literature review. The literature review is a comprehensive review of a particular topic that is not the result of a field study. While the method he uses is content analysis. Content analysis is looking for data sources from journals, scientific articles, and books. The results of the research are that Islamic education based on the value of monotheism can be interpreted as an effort made in optimizing the potential of students so that they are united with the belief in the Oneness of Allah SWT. So that if it is related to Islamic education material, the rationale will always be related to the values ​​of monotheism. The implications of education based on the value of monotheism can be in the form of 1) creating a curriculum based on the value of monotheism. 2) the presentation of material in any field of science is related to the value of monotheism. 3) learning is carried out with more emphasis on holistic thinking for both educators and students.